Effectiveness of High Dosage of Calcium, Folic Acid and Vitamin D on Reducing the Risk of Preeclamsion Among Pregnant Women - Rizki, Arkanthi Chandra; Mochartini, Tri (STIKep PPNI Jawa Barat, 2024)
Aims: to determine the effectiveness of giving high doses of calcium, folic acid and vitamin D to reducing the risk of preeclampsia in the Karawang Health Center in 2023. Methods: the type of research used in this research is quantitative with a cross sectional research design. The population in this study were 68 pregnant women who were at the Karawang Health Center, Karawang Regency. a sample of 45 pregnant women who were at the Karawang Community Health Center in Karawang Regency and bivariate analysis using the chi-square test. Results: Most of the use of high-dose calcium were adherent by 26 people (67.8%), most of the use of folic acid were adherent by as many as 30 people (66.7%), most of the use of vitamin D were not adherent by 27 people (60.0%). Most of the risk of preeclampsia blood pressure in normal pregnant women as many as 25 people (55.6%). Giving high doses of calcium, folic acid and vitamin D is effective in reducing the risk of preeclampsia in the Karawang Health Center in 2023 with (P-Value ≤ 0.05). Conclusion: It can be concluded that giving high doses of calcium, folic acid and vitamin D is effective in reducing the risk of preeclampsia in the Karawang Health Center in 2023.